Endoscopic papillary large balloon dilation in patients with large biliary stones and periampullary diverticula: Results of a multicentric series. Issue 8 (August 2018) - Zulli, Claudio; Grande, Giuseppe; Tontini, Gian Eugenio; Labianca, Orazio; Geraci, Girolamo; Sciumè, Carmelo; Antypas, Pavlos; Fiocca, Fausto; Manes, Gianpiero; Devani, Massimo; Manta, Raffaele; Maurano, Attilio
Abstract: Introduction: Stone extraction represents the most frequent indication for endoscopic retrograde cholangiopancreatography (ERCP). Endoscopic papillary large balloon dilation (EPLBD) is a recent introduced approach consisting of an endoscopic papillary large balloon dilation following limited endoscopic sphyncterotomy (ES), which has been proven to be safe and effective for extraction of large common bile duct (CBD) stones. Peri-ampullary diverticula (PAD) are described in 10–20% of patients undergoing ERCP. Aim of our study is to evaluate efficacy and safety of EPLBD for the extraction of large biliary stones in patients with PAD. Methods: The prospectively collected endoscopy databases of 4 Italian ERCP high-volume centers were reviewed retrospectively, and all consecutive patients with an instrumental diagnosis of large biliary stones and PAD, between September 2014 and October 2016, were included in this study. Results: Eighty-one patients (36 males, median age 75 years) were treated between September 2014 and October 2016. Deep biliary cannulation was reached in 78/80 patients. Successful extraction was achieved in 74/78 patients at the first attempt. AEs occurred in 8 patients (1 severe). Younger age, stone size and incomplete stone extraction were significantly associated with AEs. Conclusions: EPLBD is an effective and safe technique in patients with PAD and large biliary stones, which avoids the need of other techniques, thereby reducing the risks of adverse events.